2005
DOI: 10.1063/1.1852391
|View full text |Cite
|
Sign up to set email alerts
|

Defect detection in aluminum laser welds using an anisotropic magnetoresistive sensor array

Abstract: For the detection of defects in aluminum laser welds an anisotropic magnetoresistive (AMR) sensor array was implemented in an eddy current testing system. The reliability of weld testing is strongly influenced by the texture of the laser weld whose field response significantly superimposes the defect’s magnetic signature. A finite-element model was used to determine the influence of the weld’s topology on the detection of defects such as porosities and inclusions hosted in the aluminum matrix. When using an AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…B. Anlagenbau, Kraftwerkstechnik, Fertigungstechnik, Verkehrstechnik, Medizintechnik) und können mittels hochauflösender MR-Sensorik noch leistungsfähiger gestaltet werden. Es überrascht demnach nicht, dass in den beiden letzten Jahren eine rasant ansteigende Anzahl von Publikationen beobachtet werden konnte, bei denen GMR-Technologie als Schlüssel-element der elektromagnetischen Materialprüfung zum Tragen kommt [1][2][3][4][5]. Dies verdeutlicht, dass die magnetische Mikrosystemtechnik mit der GMR-Technologie in der zerstörungsfreie Prüfung einen neuen innovativen methodischen Ansatz darstellt und in den kommenden Jahren ein steigender Bedarf an adaptierten GMRSensorsystemen zu decken sein wird.…”
Section: Einführungunclassified
“…B. Anlagenbau, Kraftwerkstechnik, Fertigungstechnik, Verkehrstechnik, Medizintechnik) und können mittels hochauflösender MR-Sensorik noch leistungsfähiger gestaltet werden. Es überrascht demnach nicht, dass in den beiden letzten Jahren eine rasant ansteigende Anzahl von Publikationen beobachtet werden konnte, bei denen GMR-Technologie als Schlüssel-element der elektromagnetischen Materialprüfung zum Tragen kommt [1][2][3][4][5]. Dies verdeutlicht, dass die magnetische Mikrosystemtechnik mit der GMR-Technologie in der zerstörungsfreie Prüfung einen neuen innovativen methodischen Ansatz darstellt und in den kommenden Jahren ein steigender Bedarf an adaptierten GMRSensorsystemen zu decken sein wird.…”
Section: Einführungunclassified
“…The AMR sensor is advantageous over the coilbased magnetic sensor owing to its sensitivity from DC to a few kHz. To construct the ECT system, many magnetometers have been used, such as inductive coil, 18 hall sensor, 19 Tunnelling Magnetoresistance (TMR) sensor, 13,20 anisotropic magnetoresistance (AMR) sensor, 21,22 fluxgate and superconducting quantum interference device (SQUID). 22 A study shows that SQUID has the lowest noise compare to other sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the new differential eddy current testing sensor is suggested which consists of two magnetic sensors with the excitation coil. In the beginning, this research started with an AMR sensor [13,14] which means it only contained a single absolute probe. This sensor module was used in the first attempt of the study to integrate the magnetic field sensor into the ECT probe but when the scanning process was conducted, it is found that the measured signal contained metal and background signals which could be assumed as noises.…”
Section: Introductionmentioning
confidence: 99%